Linking Theories of Framing and Collective Identity Formation: Women’s Organizations’ Involvement with the Supramed Strike - Taylan Acar (European Journal of Turkish Studies)
Framing, in social movement studies, has been conceptualized as a strategic attempt of movement actors to make claims that resonate within the existing context. This led to criticisms of the framing approach for having a descriptive bias and static tendencies, as well as for lacking systematic empirical studies. Linking framing theories with the diffusion and identity formation processes, this paper develops a theoretical understanding of the framing approach with more space for contingency and relationality. Relying on a case study on the Supramed strike in a free trade zone context in Antalya, Turkey, where all but two workers were women, I analyze the frame extension of the strike from a classical unionist narrative towards a women’s liberation one. The main purpose of the paper is to understand how the collective identity of “working women” was constructed through the diffusion process and feminist activists’ involvement with the strike. I argue that the frame extension to a women’s liberation perspective took place as a result of mutual and dynamic interaction between women workers and feminist organizations, which was contingent upon various factors, such as the women’s journal of the union organized in the factory; the March 8 International Women’s Day celebrations, which provided the initial contact between the workers and feminists; and the formation of the Women’s Solidarity Platform.